Theoretical-methodological construction of a research: an analysis of the path traveled (Research, Society and Development, 2021)
Mastering scientific research methodologies can be one of the biggest challenges in the development of scientific work. However, knowledge of the proper methods to carry out a research is extremely important for the project to have scientific relevance. This article is an excerpt from the ongoing research entitled “The profile of a public school in Humaitá-Am: an analysis of the Saeb's performance and the relationship with pedagogical practices”, research proposed for the research line, theoretical-methodological perspectives for the teaching of human sciences of the Graduate Program in Teaching of Science and Humanities (PPGECH) of the Federal University of Amazonas (UFAM), which will provide, to analyze in the context of a public school with better performance in the SAEB (2019), practices that favor the quality of teaching and learning. This cut will seek to describe the methodological path chosen for the research, conceptualizing theoretically, pointing out its importance for the research. The theoretical-methodological adjustment presented is based on considerations in the domain of the Education Research discipline.